Cointegration between palm oil price and soybean oil price: A study on market integration - Mohammad Haji Alias ,; Jamal Othman, (Penerbit Universiti Kebangsaan Malaysia, 1998)
The main objective of the paper is to present a cointegration approach to ascertain whether there exists a long run relationship between palm oil price and soybean oil price. A related objective is to investigate causality patterns between the two price series using the Granger causality test. The study establish that the time series on palm oil and soybean oil prices are cointegrated even though separately, each time series is non-stationary. This suggests there exists a long run time series is non-stationary. This suggests there exists a long run equilibrium relationship between the two variables. Bidirectional causality is established at the 5 per cent level of significance for the causality is established at the 5 per cent level of significance for the F-test, however, at the 1 per cent level of significance, a unidirectional causality from soybean oil price to palm oil price is established